Description of the female of Eilica pomposa (Araneae, Gnaphosidae) with new records and notes on species distribution - Ott, Ricardo; Rodrigues, Everton Nei Lopes (Zootaxa, 2011)
The genus Eilica Keyserling, 1891 is worldwide distributed including 28 species (Platnick, 2011). South American Eilica are represented by 10 species of which seven are known by more meridional distribution: E. amambay Platnick, 1985; E. maculipes (Vellard, 1925); E. modesta Keyserling, 1891 E. myrmecophila (Simon, 1903); E. pomposa Medan, 2001; E. trilineata (Mello-Leitão, 1941) and E. uniformis (Schiapelli & Gerschman, 1942). Eilica pomposa was described from Argentina based on only two known males collected around 1000 km apart from each other in a considered suspect wide distribution by Medan (2001:404). In this paper we describe and illustrate for the first time the female of E. pomposa and present notes on its natural history and distribution.